Tailoring the electrical and thermal conductivity of multi-component and multi-phase polymer composites. (2nd April 2020) - Huang, Yao; Ellingford, Christopher; Bowen, Chris; McNally, Tony; Wu, Daming; Wan, Chaoying
ABSTRACT: The majority of polymers are electrical and thermal insulators. In order to create electrically active and thermally conductive polymers and composites, the hybrid-filler systems is an effective approach, i.e. combining different types of fillers with different dimensions, in order to facilitate the formation of interconnected conducting networks and to enhance the electrical, thermal, mechanical and processing properties synergistically. By tailoring polymer-filler interactions both thermodynamically and kinetically, the selective localisation of fillers in polymer blends and at the interface of co-continuous polymer blends can enhance the electrical conductivity at a low percolation threshold. Moreover, selective localisation of different filler types in different co-continuous phases can result in multiple functionalities, such as high electrical conductivity, thermal conductivity or electromagnetic interference shielding. In this review, we discuss the latest progress towards the development of electrically active and thermally conductive polymer composites, and highlight the technical challenges and future research directions.